2018
DOI: 10.1093/cid/ciy264
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Burden of Depression and All-Cause Mortality in Women Living With Human Immunodeficiency Virus

Abstract: In this sample of WLWH, increased CDWD elevated mortality rates in a dose-response fashion. More frequent monitoring and enhanced depression treatment protocols designed to reduce CDWD may interrupt the accumulation of mortality risk among WLWH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 33 publications
0
14
0
1
Order By: Relevance
“…Substance use disorders (alcohol, injection drugs and non‐injection drugs) among PLWH are also a growing concern in SSA . While mental health and substance use disorders are associated with suboptimal HIV treatment outcomes, including late ART initiation, poor ART adherence, lack of viral suppression and increased AIDS‐related mortality , the coverage of screening, diagnosis and treatment services for these disorders is extremely limited in SSA . Key constraints include workforce shortages, limited training on mental health and substance use disorders, the lack of validated and culturally appropriate screening and diagnostic tools, as well as the lack of proven treatment interventions that can be integrated into HIV care and delivered by non‐specialists in contexts facing mental health and substance use workforce challenges . Research approaches: The magnitude of mental health and substance use disorders merits further study, along with the effects of integrated treatment for these disorders on HIV outcomes under Treat All .…”
Section: Resultsmentioning
confidence: 99%
“…Substance use disorders (alcohol, injection drugs and non‐injection drugs) among PLWH are also a growing concern in SSA . While mental health and substance use disorders are associated with suboptimal HIV treatment outcomes, including late ART initiation, poor ART adherence, lack of viral suppression and increased AIDS‐related mortality , the coverage of screening, diagnosis and treatment services for these disorders is extremely limited in SSA . Key constraints include workforce shortages, limited training on mental health and substance use disorders, the lack of validated and culturally appropriate screening and diagnostic tools, as well as the lack of proven treatment interventions that can be integrated into HIV care and delivered by non‐specialists in contexts facing mental health and substance use workforce challenges . Research approaches: The magnitude of mental health and substance use disorders merits further study, along with the effects of integrated treatment for these disorders on HIV outcomes under Treat All .…”
Section: Resultsmentioning
confidence: 99%
“…Higher frequency of depression has been repeatedly documented in HIV+ compared to HIV-negative (HIV-) subjects: a 2001 meta-analysis found the frequency of MDD to be nearly two times higher in HIV+ subjects (27), with more recent work confirming that figure (1, 28, 29). Beyond the psychological toll of depression in HIV+ subjects, the ramifications extend to its impact on survival, mainly through its effect on treatment adherence (30) and secondary control of the infection: untreated depression was associated with significantly decreased odds of achieving >90% adherence to HAART and significantly lower odds of controlling HIV RNA levels to <500 copies/ml (31).…”
Section: Discussionmentioning
confidence: 97%
“…Prior studies investigating depression and mortality among people with HIV infection have reported increased mortality risk among those with depression diagnoses or questionnaire‐based depressive symptoms , with some exceptions . Some studies focused on multiple mental health and/or substance use disorders , while others investigated joint effects of depression and antiretroviral therapy adherence on mortality .…”
Section: Discussionmentioning
confidence: 99%